Dose evaluation in medical staff during interventional radiology procedures - Bacchim Neto, Fernando Antonio [UNESP] (2015)
Interventional Radiology is the radiology modality that provides the highest dose values to medical staff. Recent researches show that personal dosimeters may underestimate dose values in interventional physicians, especially in extremities and eye lens. The aim of this work was to study radiation exposure levels of medical staff in different hemodynamics interventional radiology procedures. Dosimeters were positioned in different body regions of the interventional physician. Dose values were compared with annual dose limits for workers thus finding the maximum number of annual procedures that each physician could perform. As each body region of the interventionist is subject to different levels of exposure, dose distribution in each region provides a better approach to what actions are necessary to ensure the radiological protection of medical staff.